Cardiovascular risk scores among workers assisted at a Workers' Health Reference Center (Research, Society and Development, 2022)
This study seeks to identify the risk of developing a cardiovascular disease in ten years among workers assisted at a Reference Center for Occupational Health. For that purpose, the Risk Score developed by the World Health Organization and the International Society of Hypertension (WHO/ISH) was applied. This is a longitudinal, retrospective, dynamic population study, carried out with secondary data obtained from a nutrition clinic located in the city of Salvador, which serves workers with occupational disease in the state of Bahia, Brazil. Risk Score calculation is based on known risk factors for cardiovascular disease, gender, age, presence or absence of diabetes, in smokers or non-smokers alike, systolic blood pressure and total cholesterol levels. For ease of presentation and understanding, the Risk Score was analyzed as: a) low - less than 10% risk; b) moderate/high – greater than or equal to 10%. Results show that, in the first consultation, workers showed evidence of moderate/high risk for CVD among women aged over 50 years, with alcohol and tobacco consumption habits, with over 9 years of education and who did not practice physical activity. Regarding anthropometric, biochemical and blood pressure characteristics, obese individuals with total cholesterol, triglycerides, systolic pressure and abdominal perimeter above normal parameters are in the moderate/high group for cardiovascular disease. It is concluded that appropriate interventions capable of addressing the various social, cultural and emotional aspects, among others, are necessary, which can increase the workers' level of information, helping them to improve their health.